2005
DOI: 10.5194/angeo-23-2457-2005
|View full text |Cite
|
Sign up to set email alerts
|

VHF and L-band scintillation characteristics over an Indian low latitude station, Waltair (17.7° N, 83.3° E)

Abstract: Abstract. Characteristics of simultaneous VHF (244 MHz) and L-band (1.5 GHz) scintillations recorded at a low-latitude station, Waltair (17.7° N, 83.3° E), during the low sunspot activity year of March 2004 to March 2005, suggest that the occurrence of scintillations is mainly due to two types, namely the Plasma Bubble Induced (PBI), which maximizes during the post sunset hours of winter and equinoctial months, and the Bottom Side Sinusoidal (BSS) type, which maximizes during the post-midnight hours of the sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…Deng et al (2013) have reported that during a rising solar activity period, the annual mean patch duration over South China varies between 10 and 180 min with the most probable value between 10 and 60 min. The results obtained from the present study are in close agreement with those of previous studies by Rama Rao et al (2005) and Prasad et al (2001) over the Waltair station and Deng et al (2013) over South China. Zou (2011) observed a small amount of scintillation events during the daytime at Guilin.…”
Section: Duration Distribution Of Scintillation Patchessupporting
confidence: 95%
“…Deng et al (2013) have reported that during a rising solar activity period, the annual mean patch duration over South China varies between 10 and 180 min with the most probable value between 10 and 60 min. The results obtained from the present study are in close agreement with those of previous studies by Rama Rao et al (2005) and Prasad et al (2001) over the Waltair station and Deng et al (2013) over South China. Zou (2011) observed a small amount of scintillation events during the daytime at Guilin.…”
Section: Duration Distribution Of Scintillation Patchessupporting
confidence: 95%
“…On 14 October and 6 November 2011, although Fresnel's oscillation is observed at RPMC, the same is found to be absent at BOK. Presence of Fresnel's oscillations in the power spectra may be indicative of a thin layer of irregularities of thickness < 100 km (Rama Rao et al, 2005). The available ionosonde data revealed range spread F (RSF) in pre-to post-midnight hours preceding the VHF scintillation in almost every case with the maximum h F lying in the range hours.…”
Section: Spectral Features Of Scintillation Variabilitymentioning
confidence: 99%
“…Total Electron Content (TEC) is an important ionospheric parameter which directly affects the propagation of radio waves through the ionosphere. In the equatorial region, the TEC gradient may be one cause of the equatorial bubbles phenomenon (Yeh et al, 1979;Das Gupta et al, 1983;Rama Rao et al, 2004). TEC measurements assist in the development of ionospheric models, such as the International Reference Ionosphere (IRI) (Bilitza, 2001;Bilitza and Reinisch, 2008).…”
Section: Introductionmentioning
confidence: 99%